Anaesthetic mouthpiece development through QFD and customer interaction with functional prototypes - Booysen, G.J.; Barnard, L.J.; Truscott, M.; de Beer, D.J. (Rapid prototyping journal, 2006)
Purpose - The paper reflects on the development of a medical product using rapid prototyping technologies and customer interaction through a quality function deployment (QFD) approach to speed up the process, and to result in customer satisfaction. The purpose of the specific medical product was to develop a device for fixing an Endo-tracheal (ET) tube in a patient during anaesthesia, as it is common for an ET tube to move and or become dislodged due to various extraneous reasons. If the tube deviates from the correct position it can cause one or both lungs to collapse, which can be fatal. The paper reviews how the anaesthetist's idea, which was to develop a product that could hold an ET tube in place in a more secure manner than is possible with current technologies, was brought to fruition through customer interaction.Design methodology approach - Using an action-research approach, the design evolved through series of design concepts, which through customer interaction contributed to a total optimized design. Virtual and physical prototypes, together with silicone mouldings were used as part of the customer interaction.Findings - As with any new product, some functional parts were needed to conduct tests, which in turn would help to prove the product, and hence, the design. Traditionally this meant the manufacturing of a hard tool and proving of the design through trial and error. Hard tooling allows for some small changes to be made, but if the changes are radical a new tool will have to be designed and manufactured.Research limitations implications - Following a developmental approach through the application of various types stages of prototyping (such as virtual prototypes), revolutionised this process by simplifying and accelerating the development iteration process - it also developed a new version paradigm of QFD.Practical implications - Opposed to traditional forms of QFD where customer inputs are gathered through questionnaires, this case study proved that functional models provide an efficient client-feedback, through constant involvement in the development process, as well as evaluation of the systematic progress.Originality value - The case study shows that experts in other disciplines can become involved in the product development process through the availability of functional prototypes, and builds on previous work to introduce a concept of customer interaction with functional prototypes.